The Importance of Educational Psychology for Education and its Contribution to Education - Hadi, Samsul; Alfia Nursyamsi, Nina; Adelia, Amanda Putri (Berpusi Publishing, 2023)
This article intends to explain and provide information to readers about the importance of educational psychology for educators and its contribution to education. Educational psychology is a field of psychology that studies the phenomena of psychological dynamics and individual behavior in the educational process (Strickland, 2001). Currently, there are many students who experience problems but can only remain silent without telling other people, as a result they cannot focus on seeking knowledge and have inappropriate behavior. From this statement, teachers must be able to understand how important educational psychology is in the educational environment. Because the role of teachers is apart from guiding and providing knowledge, they must also understand each student's inner self, so that they can understand the problems experienced by their students and teachers must be able to provide solutions and direct them in a better direction. If every teacher could understand the behavior of their students, perhaps this would rarely happen and children would feel better and not feel stressed because they could talk about their problems, especially to a teacher. With problems like this, we tried to conduct research using the library research method so that we could find out how important educational psychology is for an educator and its contribution to education.